EFFORTS TO IMPROVE SOCIAL SCIENCE (IPS) LEARNING ACHIEVEMENT THROUGH THE STAD LEARNING MODEL FOR GRADE IX A STUDENTS OF UPT SMPN 25 GRESIK ACADEMIC YEAR 2021/2022 - S Tri Wahyuningsih (LPPM STAI Muhammadiyah Probolinggo, 2022)
The quality of teaching and learning activities is not only observed in terms of results, but also must be surveyed from the process. The quality of the teaching and learning process is characterized by the level of student participation in teaching and learning activities. The level of student participation in teaching and learning activities could always be improved when the teacher attempts to utilize teaching strategies effectively to improve the quality of teaching and learning activities from the aspect of the process. Thus, the quality of the process from the aspect of the results will increase, or it could be mentioned as the improvement of student achievement.Based on the reasons or background of the problems, the author is interested in conducting class action research with the title